Strategi Kesuksesan Pertumbuhan Pasar Swalayan Studi Kasus: Toko Mini Market di Kota Pekanbaru - Khaidir Saib (Universitas PGRI Madiun, 2019)
The determinants of success are the elements that shape to achieve success in competition for companies in the world of commerce. Success shows the performance of whether the company has succeeded or has not succeeded in achieving its mission and vision goals set before the company was established. companies that successfully identify and use specific strategies will enable them to achieve competitive advantage. This study focuses on the determinants of the successful growth of Mini market in Pekanbaru City. For this purpose 10 mini market entrepreneurs Mini market have been selected as respondents. This study aims to identify the determinants of success of Mini Marekt entrepreneurs. Data collection methods were conducted through interviews with management and company officers. The findings indicate that the three key determinants of the success of inddomaret and alfamart are the skill of reading the market sgement, specializing in opening a business and also the courage to face business challenges.